EVALUASI STRUKTUR PASCA KEBAKARAN ASRAMA SANTRI PONDOK PESANTREN DARUL QUR’AN, WONOSARI, GUNUNGKIDUL, YOGYAKARTA - Agus Susanto (TEKNISIA, 2016)
Student dormitory building of Darul Qur’an Islamic Center was burned on Wednesday, January 6th, 2016 at around 00:15 am to 02.15 am. Building damaged by fire, often directly considered as no longer useable and sometimes being destroyed. This resulted in inefficiency and bad for the environment, either in the form of building waste, and the extraction of natural resources for building materials. Evaluation on post-fire structure is very important for reference in decision making on further action on the building so that the action is optimal and can be scientifically responsible.This research was conducted in two stages: data collection and data processing. Data collection was done by direct survey to location, collecting building design documents, doing interview with the witnesses and dormitory caretaker, visual observation, testing the existing concrete structure strength using Schmidt Hammer Test, and measuring the structural displacements using Theodolite. Then, these field test result were being processed to produce the compressive concrete strength (fc’) and beam deflection. This calculated fc’ were used as input for structural analysis of the existing structure using ETABS software.The study concluded that the existing structure is no longer able to withstand the requisite load corresponding to building function as dormitoryaccording to regulation (SNI 2847: 2013). Fire have caused some of structural reinforcement steel melted which caused the beam deflections exceed the limit allowed by building code, and the structural serviceability decreased.The quality of construction was poor and not uniform, resulting in some trouble since beginning, problems alsooccurred in building utilities. The study suggested that structural retrofitting was required on parts of the structure that had been damaged, but even if we don’t repair the structure, the building still can be used, but with decreased usage load. The structure needs to be evaluated periodically.